Religion, community, and education : the case of rural Bihar - Alam, Sanjeer (New Delhi ; Oxford : Oxford University Press, 2012)
This work assesses literacy and educational levels among Hindus and Muslims in rural Bihar as well as the disparity therein. It is based on extensive fieldwork conducted in the state, covering 300 households and 700 schoolchildren.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Keywords: Educational equalization -- India -- Bihar; Education, Rural -- India -- Bihar; Hindus -- Education -- India -- Bihar; Muslims -- Education -- India -- Bihar; Literacy -- Religious aspects; Literacy -- India -- Bihar